Strengthening the Culture of Computational Thinking through VR Game-based Learning in Vocational High School - Pramudita, Dias Aziz; Hermawan, Hardika Dwi; Sukirman; Nisa, Anis Khoerun; Permana, Adira Bintang (Buletin Literasi Budaya Sekolah, 2025)
Computational Thinking (CT) is an essential competence for students in vocational education to support problem-solving, systematic thinking, and adaptability to workplace demands. However, the development of CT in vocational high schools is often limited to technical instruction and has not been fully integrated into students’ learning culture. This study aims to examine the role of Virtual Reality (VR) Game-Based Learning in strengthening the culture of computational thinking among vocational high school students. The study focuses on how VR-based game learning activities foster habitual patterns of logical, systematic, and problem-solving thinking within vocational classroom practices. Using a qualitative descriptive approach through classroom observations, analysis of learning activities, and student reflections, this research explores changes in student engagement, learning interactions, and thinking habits during the implementation of VR Game-Based Learning. The findings indicate that VR-based games create an immersive and contextual learning environment that encourages active participation, collaboration, and sustained engagement, contributing to the formation of a computational thinking culture relevant to vocational learning contexts. This study suggests that VR Game-Based Learning can function as an effective pedagogical practice to support the development of a positive learning culture aligned with the needs of vocational education.